2008
DOI: 10.1002/jnr.21779
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new markers for neurodegeneration process in the mouse model of Sly disease as revealed by expression profiling of selected genes

Abstract: Sly disease (MPS VII) is an autosomal-recessive lysosomal storage disorder resulting from beta-glucuronidase deficiency, which is characterized by a severe neurological impairment. MPS VII mice accumulate undegraded glycosaminoglycans and mimic the human neurodegenerative disorder, thus appearing to be an excellent tool to delineate disease pathogenesis. The relationship between abnormal glycosaminoglycan storage and neurodysfunction is not yet well understood, but inflammatory components can be involved, as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…When MPSII mice were analyzed at 6 months of age, i.e., 4 months after administration of AAV9-Ids vectors, the content of GAGs, the general and ultrastructural aspect, and the size and function of brain lysosomes were all corrected in treated animals, but these had worsened in nontreated MPSII animals or those receiving noncoding AAV9-Null vectors. Two-month-old untreated MPSII mice also showed pronounced astrocytosis and microgliosis throughout the brain, a hallmark finding in different animal models of mucopolysaccharidoses that present with neurodegeneration (38,40,52,54,(68)(69)(70) and in Hunter syndrome patients (47,48). The effects of AAV9-mediated IDS gene transfer on the transcriptional signature and histological findings associated with microglial activation in 6-month old animals were quite striking and were in agreement with our previous observations in MPSIIIB mice (40).…”
Section: Discussionsupporting
confidence: 90%
“…When MPSII mice were analyzed at 6 months of age, i.e., 4 months after administration of AAV9-Ids vectors, the content of GAGs, the general and ultrastructural aspect, and the size and function of brain lysosomes were all corrected in treated animals, but these had worsened in nontreated MPSII animals or those receiving noncoding AAV9-Null vectors. Two-month-old untreated MPSII mice also showed pronounced astrocytosis and microgliosis throughout the brain, a hallmark finding in different animal models of mucopolysaccharidoses that present with neurodegeneration (38,40,52,54,(68)(69)(70) and in Hunter syndrome patients (47,48). The effects of AAV9-mediated IDS gene transfer on the transcriptional signature and histological findings associated with microglial activation in 6-month old animals were quite striking and were in agreement with our previous observations in MPSIIIB mice (40).…”
Section: Discussionsupporting
confidence: 90%
“…3F). TNF-α is an important downstream mediator of TLR4, and several investigators have recently shown that TLR4 activation and/or TNF-α has important pathogenic effects in the brains of MPS mouse models (6,25). We therefore examined the locomotor behavior of the DKO mice using an accelerating rotarod (Fig.…”
mentioning
confidence: 99%
“…The observation that the increase of these mediators was accompanied by progressive microglial activation and expansion supports the hypothesis that inflammation is the major cause of neurodegeneration in gangliosidoses. This microglial activation is a characteristic shared by numerous neurodegenerative diseases (Minagar et al, 2002) and other lysosomal diseases, such as MPS I, MPS IIIB (Ohmi et al, 2003), Niemann-Pick type C (German et al, 2002), Krabbe disease (Wu et al, 2000), MPS VII (Richard et al, 2008) and MPS IIIA (Arfi et al, 2011).…”
Section: Pathophysiologymentioning
confidence: 94%
“…Inflammation is known to be implicated in numerous neurodegenerative diseases, and has been recently well characterized in murine models of GM1/GM2 gangliosidoses (Myerowitz et al, 2002, Jeyakumar et al, 2003, as well as in mouse models of Metachromatic Leukodystrophy (Hess et al, 1996), Niemann-Pick C disease (German et al, 2002), MPS I (Ohmi et al, 2003), MPS IIIB (Ohmi et al, 2003;Villani et al, 2007) and MPS IIIA (Fraldi et al, 2007). Moreover, our previous study on a mouse model of MPS VII showed an extensive upregulation of genes related to an inflammatory process dominated by activated microglia, astrogliosis and celldeath, suggesting that inflammation might participate in neurodegeneration (Richard et al, 2008).…”
Section: Complementary Therapeutic Strategies Based On Downstream Comentioning
confidence: 94%